Pengaruh Citra Merek, Kualitas Produk, Dan Promosi Terhadap Kepuasan Konsumen (Studi Pada Kedai Susu Mom Milk Di Solo) - Setyawan, Muhammad Adhi; , Dra. Chuzaimah, M.M (2016)
The research was carried out in shops Moo Dairy Milk in Solo in order to know the influence of brand image on consumer satisfaction, determine the effect of product quality to customer satisfaction and know the effect of promotions on consumer satisfaction. The research method uses the entire consumer population MomMilkdi Solo Coffee Milk, with a sample size of 100 responden.Metode data retrieval gave questionnaires to consumers. Analysis Tools used: 1) Test Instruments (Test Validity and reliability), 2) Classical Assumption Test (Normality Test, Test Multicolinearity and Test Heteroskidastity), 3) Test the hypothesis (multiple linear regression analysis, t-test, F and R2 The results of data analysis can be obtained as follows: 1) states that the variable Brand (X1), Product Quality variable (X2), variable Promotion (X3) has an effect on positive and significant consumer satisfaction. 2) Based on t test showed that the value of the results of tcount variable Brand Image of 2,109, the variable quality of the product amounted to 3.131 and variable promotions by 3,904 and the value table = 1.985, this means that thitung> t table then Ho is rejected so that there is a significant effect of brand image, product quality and promotion of consumer satisfaction individually. 3) Test F shows the value Fhitung 15.182, that number means Fhitung greater than F table so that simultaneous variable Brand Image, Product Quality and Promotion significantly influence consumer satisfaction satisfaction. 4) Test (R2) is 0,322berarti Brand Image variable, variable Quality Products, Promotional variable affects customer satisfaction at Coffee Milk Mommilk 32.2% and 67.8% is explained by factors or other variables outside the model. Keywords: Brand, Quality Products, Promotions and Customer Satisfaction